Prevalence, Risk Factors and Pathogenetic Mechanisms Temporomandibular Joint Dysfunction - Astanov O.M.; Ruzieva M.I. (Scholars Digest Publishing, 2023)
This article analyzes the literature of domestic and foreign authors on the justification and implementation of a systematic approach in the diagnosis, prediction and personalized assessment of the effectiveness of treatment of TMJ dysfunction based on sociological, clinical, functional, psychological research and mathematical modeling.
Keywords: temporomandibular joint dysfunction, etiology, pathogenesis of DTMJ.